Special aspects of termination of alternative obligations according to civil legislation of Ukraine - Музика, Т. О. (Theory and practice of jurisprudence, 2016)
The article explores some general grounds for termination of obligation. It is specially noted, that legal relationships of termination of alternative obligations are not regulated by special rules of civil legislation of Ukraine. But there are some issues associated with such limited regulation, for example: when does the alternative obligation terminate by performance, which are the special features of termination of alternative obligation by remitting the debt, impossibility to execute an obligation etc. It is reported, that researches of performance of alternative obligation has been conducted by E. L. Alekhina, K. I. Bernstein, A. M. Blashchuk, V. M. Ignatenko, A. V. Kostruba, O. A. Melnychenko, M. Panchenko, V. Holevynskyi, V. S. Petrov, S. B. Sarbash, S. Yu. Filippova, O. Yu. Shylokhvost and others. The object of the paper is to analyze legislation of Ukraine and civil theory concerning termination of obligations and their peculiarities concerning alternative obligations. Much attention is given to a moment of termination of alternative obligation by performance. It is examined, that there are two established views on this issue. First view is that the alternative obligation terminates when the choice is made. The author espouses second view, according to which alternative obligation terminates by complete performance of one of its subjects. It is underlined that the aim of alternative obligation is to satisfy the creditor’s behalf and the choice is one of the stages of it. 2 Then the provisions for termination of alternative obligation by transfer of the indemnity are described. It is told that the parties’ consent must include subject which are different from performances of primary alternative obligation. Further the ways of termination of alternative obligation by novation are reported. The conditions of termination of alternative obligation by offsetting are investigated. It is stressed that it depends on making a choice by empowered party. Next the author studies provision for termination of alternative obligation by remitting the debt. Then the termination of alternative obligation through impossibility to execute it special rules are defined. At the last part of the article the author arrives at several conclusions. It is underlined, that the moment of alternative obligations’ termination by proper execution is the moment when complete performance of one of its subjects is made. Then it is noted that the choice as the specific condition of alternative obligation has influence on the termination of it by indemnity, novation, offsetting of counter-claims and remitting the debt. It is also concluded that the impossibility to execute one of the subject of performance in connection with a circumstance, for which none of the parties is responsible does not release the debtor from responsibility to perform one of the other subjects.